2009
DOI: 10.1016/j.neuroscience.2009.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cholinergic and non-cholinergic neurons in the pons expressing phosphorylated cyclic adenosine monophosphate response element-binding protein as a function of rapid eye movement sleep

Abstract: Recent studies have shown that in the pedunculopontine tegmental nucleus (PPT), increased neuronal activity and kainate receptor-mediated activation of intracellular protein kinase A (PKA) are important physiological and molecular steps for the generation of REM sleep. In the present study performed on rats, phosphorylated cAMP response element-binding protein (pCREB) immunostaining was used as a marker for increased intracellular PKA activation and as a reflection of increased neuronal activity. To identify w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 96 publications
0
51
0
Order By: Relevance
“…confirmed that the cholinergic pedunculopontine tegmental neurons are REM-on cells and serotonergic dorsal raphe nucleus and noradrenergic locus coeruleus neurons are REM-off cells 98 . It has also become clear that GABA (γ-aminobutyric acid) and glutamate participate in this process 66 .…”
Section: Box 2 | Historical Backgroundmentioning
confidence: 75%
“…confirmed that the cholinergic pedunculopontine tegmental neurons are REM-on cells and serotonergic dorsal raphe nucleus and noradrenergic locus coeruleus neurons are REM-off cells 98 . It has also become clear that GABA (γ-aminobutyric acid) and glutamate participate in this process 66 .…”
Section: Box 2 | Historical Backgroundmentioning
confidence: 75%
“…Lesion of this area produced REM sleep without muscle atonia or ponto-geniculo-occipital (PGO) waves (21,26,29,33), or diminished REM sleep (24). The SubCD is most active during REM sleep (5,13), and injection of the nonspecific acetylcholine receptor agonist carbachol (CAR) or the glutamatergic receptor agonist kainic acid (KA) into this area induced a REM sleep-like state with muscle atonia (2,28,38,44). The SubCD receives afferents from several nuclei, including the pedunculopontine nucleus (PPN) (11).…”
mentioning
confidence: 99%
“…Interestingly, one of the major brain areas in the S-W regulating network that actively regulates both W and REM sleep is the cholinergic cell compartment of the PPT (CCC-PPT) [12, 13, 136, 159]. For example, neuropharmacological and physiological studies have shown that glutamatergic activation of kainate receptors on PPT cholinergic cells induces REM sleep by raising neuronal activity to a medium level, whereas glutamatergic activation of NMDA receptors on these same PPT cholinergic cells induces W by increasing neuronal activity to its highest level [12, 130133, 159, 160].…”
Section: Possible Mechanisms Of Alcohol’s Action In Producing Sleementioning
confidence: 99%
“…It is already known that the majority of BF cholinergic cells are involved in the induction of W while the other cells are involved in the induction of SWS, but both of these cell groups suppress REM sleep [12, 171, 172]. On the other hand, activation of PPT cholinergic cells increases REM sleep [136]. Therefore, in alcohol-dependent individuals, phase advance in REM sleep could potentially be caused by the over-activation of cholinergic cells in the PPT (but not in the BF).…”
Section: Possible Mechanisms Of Alcohol’s Action In Producing Sleementioning
confidence: 99%